2017
DOI: 10.1073/pnas.1616255114
|View full text |Cite|
|
Sign up to set email alerts
|

A hypothalamic circuit that controls body temperature

Abstract: The homeostatic control of body temperature is essential for survival in mammals and is known to be regulated in part by temperature-sensitive neurons in the hypothalamus. However, the specific neural pathways and corresponding neural populations have not been fully elucidated. To identify these pathways, we used cFos staining to identify neurons that are activated by a thermal challenge and found induced expression in subsets of neurons within the ventral part of the lateral preoptic nucleus (vLPO) and the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
254
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(292 citation statements)
references
References 37 publications
22
254
3
3
Order By: Relevance
“…The temperature response to immune challenge with LPS is likely the central compilation of pyrogenic and hypothermic signaling, the neuronal substrate being reciprocally interconnected cell groups that generate temperature elevating and temperature lowering signals, respectively (Zhao et al, 2017). In the absence of induced PGE2 synthesis, animals immune challenged with LPS display hypothermia ( Fig.…”
Section: Relationship Between Fever and Hypothermiamentioning
confidence: 99%
“…The temperature response to immune challenge with LPS is likely the central compilation of pyrogenic and hypothermic signaling, the neuronal substrate being reciprocally interconnected cell groups that generate temperature elevating and temperature lowering signals, respectively (Zhao et al, 2017). In the absence of induced PGE2 synthesis, animals immune challenged with LPS display hypothermia ( Fig.…”
Section: Relationship Between Fever and Hypothermiamentioning
confidence: 99%
“…Intriguingly, this location is identical to the location of BDNF/PACAP neurons activated by heat-exposure in Tan et al (2016), raising the possibility that at least the vasodilation component of the hypothermic response observed in Tan et al was due to activation of glutamatergic neurons that express BDNF/PACAP. Interestingly, Tan et al (2016) reported that 69% of BDNF VMPO neurons, and 83% of all heat-activated VMPO neurons, are GABAergic, while Zhao et al (2016), reported that two-thirds of MnPO neurons that express Fos during heatexposure also express BDNF, but that only a third of MnPO BDNF neurons express vesicular GABA transporter (VGAT), with the remainder expressing vesicular glutamate transport 2 (VGluT2) [5]. Taken together, these data suggest that there is a population of glutamatergic BDNF/PACAP neurons which our results suggest may constitute a specific vasomotor thermoregulatory pathway.…”
mentioning
confidence: 99%
“…One possible route would be that direct projections from glutamatergic MnPO neurons to the DHA/DMH, and the medullary raphe and parapyramidal region, may represent inputs to local inhibitory neurons within these targets that modulate the activity of sympathoexcitatory output neurons [3]. Alternatively, inputs from glutamatergic MnPO neurons to inhibitory GABAergic neurons in the lateral preoptic area (LPO) [1][2][3][4][5] and the periaqueductal gray matter may result in inhibition of sympathoexcitatory pathways that conserve heat.…”
mentioning
confidence: 99%
“…Warm and cold ambient temperature both stimulate POA neurons [3, 4, 6, 33, 35, 37, 38, 44] by activating warm- or cold-sensitive neurons (WS or CS), respectively. Neuronal cold sensitivity may be due to decreased synaptic inhibition onto CS neurons by WS GABAergic neurons [4547].…”
Section: The Poa In Thermoregulation and Energy Homeostasismentioning
confidence: 99%
“…Traditionally, the POA is not associated with body weight control, but its major role in temperature-dependent metabolic adaptations warrants further investigation and discussion on the interaction between the POA and body weight homeostasis. Recent studies have used sophisticated genetic and molecular tools to shed new light on the physiological function of the POA and confirmed the robust effect of the POA on energy expenditure [36]. Most notably, POA-mediated metabolic adaptations also induced food intake and body weight changes [3].…”
Section: Introductionmentioning
confidence: 99%